2011
DOI: 10.17843/rpmesp.2011.283.532
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalencia de hepatitis viral B en estudiantes universitarios en Abancay, Perú

Abstract: realizamos un estudio transversal en 240 estudiantes de tres universidades, entre enero a octubre de 2010. Previo consentimiento informado, se llenó, por cada estudiante, una ficha epidemiológica y se tomó una muestra sanguínea para determinar la presencia de HBsAg, anti-HBcAg total, anti-HBe, HBeAg e IgM anti-HBc por el método de ELISA. Se encontró una prevalencia de 2,5 % (seis seropositivos) para el HBsAg y 28,3 % (68 seropositivos) para los anticuerpos Anti-HBcAg. El sexo masculino estuvo asociado con la p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…On other hand in a study by Sultanik et al, 2016 [14] showed that 3.38% (6/177) were anti-HDV antibodies carriers while conducting their study on HDV seroprevalence population of HBsAg carrying blood donors. The prevalence of our study is higher as compared to others as Ramírez-Soto et al [15] reported that the antidelta antibody prevalence rate of 11.2% among healthy HBsAg carriers. Some other old studies also reported lower prevalence of delta virus in HBV reactive cases as in Saudi blood donors reported rates of 8%, 5.4%, and 6.7% by Goyal et al, [16], Sagnelli et al, [17] and El-Hazmi and Wang et al [18] from Saudi Arabia and also 3.8%, 0.5%, and 5% from the United States, and Canada [19].…”
Section: Discussioncontrasting
confidence: 72%
“…On other hand in a study by Sultanik et al, 2016 [14] showed that 3.38% (6/177) were anti-HDV antibodies carriers while conducting their study on HDV seroprevalence population of HBsAg carrying blood donors. The prevalence of our study is higher as compared to others as Ramírez-Soto et al [15] reported that the antidelta antibody prevalence rate of 11.2% among healthy HBsAg carriers. Some other old studies also reported lower prevalence of delta virus in HBV reactive cases as in Saudi blood donors reported rates of 8%, 5.4%, and 6.7% by Goyal et al, [16], Sagnelli et al, [17] and El-Hazmi and Wang et al [18] from Saudi Arabia and also 3.8%, 0.5%, and 5% from the United States, and Canada [19].…”
Section: Discussioncontrasting
confidence: 72%
“…The program began with immunization of 3791 children aged under 5 years between 1991 and 1994, and subsequently expanded to universal vaccination in Abancay as well as other hyperendemic provinces in Peru [10]. Following implementation of the program against HBV, the carrier rate of HBsAg decreased from 9.8% in 1991 (in the general Abancay population) [11] to below 3% in 2010 among those aged �18 years (including 2.5% and 1.9% of university students and blood donors, respectively) [12,13]. Over the next 22 years, this vaccination program has also led to a decline in the mortality burden of HBV-related liver diseases, particularly cirrhosis and fulminant hepatitis, in children aged under 15 years [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of the vaccination program in terms of lower carrier rates of HBsAg in those aged �18 years and reduced mortality rates from HBV-related liver diseases [12][13][14], to date, there are no data on the impact of the HBV vaccination program on the carrier rates of HBsAg, hepatitis B core antibody (anti-HBc), hepatitis B surface antibody (anti-HBs) and hepatitis D antibody (anti-HDV) in the general population of Abancay. Therefore, in this study, we determined the prevalence of HBV and HDV infections in Abancay province 23 years since the introduction of the first pilot vaccination program against HBV, as well as the postvaccine response against hepatitis B in terms of prevalence of anti-HBs.…”
Section: Introductionmentioning
confidence: 99%